Islamic Perspective About Women's Reproductive Health Rights - Masykuroh, Siti; Effendi, Effendi (Universitas Islam Negeri Raden Intan Lampung, 2022)
The issue regarding the reproductive system is an important topic within gender discussion. Discrimination against women often results in violence, which one of the forms is the violence of the female reproductive system. Most Indonesian women have not earned the full rights of their reproductive health. It is not yet recognized by most Indonesian women that the rights of the reproductive system are autonomic which indicates that each individual must own the right completely.The issue regarding the fulfillment of the female reproductive system is usually described in fiqh doctrine which tends to be gender biased. If we are able to analyze the issue deeper, the Al Qur'an's doctrine gives a proper analysis regarding the health of the reproductive system. Within surah An Nisa', Allah highlighted that men and women are given an equal responsibility to grow humanity. It is clearly stated within the holy Al Qur'an that woman's rights must be held responsible, respected, and protected. As an example, the holy Al Qur'an forbidding to conduct sexual intercourse with women during their period. Another example is that holy Al Qur'an explained that pregnant and breastfeeding women are in their vital stage, and they must be protected.As there are different doctrines between the fiqh and al-Qur'an regarding the issue of the female reproductive system, it is clear that the gender position of women within fiqh becomes an essential topic to discuss. We need to dig deeper as well as to develop a new understanding of fiqh, which is fiqh's gender responsiveness, as we believe that fiqh discussion must develop from time to time, following the modern human rights discourse.